«A model library» is a core of new educational space for libraries of military pre-vocational schools and comprehensive schools with cadet classes - O. R. Starovoitova (Библиосфера)
The article contains a description of possible applications of M. A. Rozov’s social relay-race theory in library activities of military schools and comprehensive schools with cadet classes. It describes in details the project «Cadethood: Information. Education. Reading», which is realized based on theories by M. A. Rozov, A. B. Antopolsky and A. A. Akhayan. We used papers by E. N. Guseva, the first national library science researcher, who introduced M. A. Rozov’s theory to the library professional community. The project structure and each element using technology are represented.